Морфологічні та екологічні особливості молюсків підродини Physinae (Mollusca: Gastropoda: Pulmonata) України - Гарлінська, Алла; Garlinska, Alla (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто деякі особливості морфологічної будови (конхіологічна та анатомічна) молюсків підродини Physinae (Gastropoda: Pulmonata) України та визначено екологічні преферендуми для цих тварин за найважливішими чинниками водного середовища. Анализ морфологических параметров видов подсемейства Physinae, как и анализ алозимной изменчивости, доказывает, что в фауне Украины это подсемейство представ¬лено тремя видами − Physa fontinalis, Ph. skinneri, Phys. acuta. The result of the complex conchology, and genetic research of the Ukrainian shellfish allowed to allocate three morphologically and evolution-genetic discret groups of shellfish Ph. fontinalis, Ph. skinneri, Phys. acuta. The greatest number of species Physinae found in the basins of the Dniester and the Danube, and the smallest - in the South Bug River Basin and the rivers of the Crimea. Western Bug, Dnieper and Seversky Donets occupy an intermediate position. All representatives of the subfamily Physinae can be divided into two groups: those that are common in the southern part of our state (Phys. acuta, Ph. skinneri), and those that are common in the northern part of it (Ph. fontinalis). Physinae favorable conditions exist at small values of water depth (0,6 m). Physinae is optimal for pH of water within 7,2−8,7. Favorable conditions exist, they are at 4,8 mg O2/l.
Morphological and Ecological Peculiarities of Ukrainian Subfamily Physinae (Mollusca: Gastropoda: Pulmonata)
Keywords: молюски; морфологічна і еволюційно-генетична дискретність; поширення; екологічні особливості; mollusks; morphological and evolution-genetic discretion; diffusion; ecological peculiarities